1998
DOI: 10.1002/hep.510280305
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the selection of phosphatidylcholine molecular species for secretion into bile in the rat

Abstract: Certain phosphatidylcholine (PC) molecular species appear to be secreted into bile preferentially, but the mechanism for this selection remains obscure. We used multivariate analysis to examine the relationship between PC structure and the odds of secretion for individual PC species secreted into bile. PC was isolated from Folch extracts of bile and liver from rats, and individual molecular species of PC were quantified with reverse-phase highperformance liquid chromatography (HPLC). The odds of secretion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Both StarD10 and Pctp are particularly abundant in the liver, where they may be involved in export of lipids into bile (47,48). The presence of high levels of StarD10 in the lactating mammary gland suggests a potential physiological role in the functional differentiation of this organ.…”
Section: Discussionmentioning
confidence: 99%
“…Both StarD10 and Pctp are particularly abundant in the liver, where they may be involved in export of lipids into bile (47,48). The presence of high levels of StarD10 in the lactating mammary gland suggests a potential physiological role in the functional differentiation of this organ.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon its accentuated expression in the liver and its high relative affinities for phosphatidylcholine molecular species that are secreted by the liver into bile [51,52], it was proposed that PC-TP might transport phosphatidylcholines from their site of synthesis in the smooth endoplasmic reticulum to the canalicular membrane of hepatocyte for secretion into bile [53,54]. In support of this possibility, in vitro studies revealed that bile salts at submicellar concentrations that might be present in hepatocytes markedly increased that activity of PC-TP [53].…”
Section: Biliary Lipid Secretionmentioning
confidence: 99%
“…Although extensive research has been done on the biophysical properties of this protein, little is known about the function of this protein in vivo. Possible physiological functions, among which is a role in bile secretion [4,5], have recently been refuted by van Helvoort et al [3]. In that study, PC-TP null mice failed to give a phenotype.…”
Section: Introductionmentioning
confidence: 99%